PENGARUH PROFITABILITAS, LEVERAGE DAN LIKUIDITAS TERHADAP KELENGKAPAN PENGUNGKAPAN SUKARELA DALAM LAPORAN TAHUNAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2016-2017 - MARBUN, GEMBIRA (Jurnal Riset Akuntansi & Keuangan, 2022)
This study aims to prove empirically whether profitability, leverage and liquidity have a significant effect on the completeness of voluntary disclosures in annual reports on manufacturing companies listed on the Indonesia Stock Exchange in 2016-2017. The population in this study are all manufacturing companies listed on the Indonesia Stock Exchange in 2016 -2017. While the sample of this study was determined by purposive sampling method in order to obtain 39 sample companies. The type of data used is secondary data obtained from www.idx.co.id. The analytical method used is multiple regression analysis with a significance level of 5%. The partial test results show that profitability and leverage have a positive and significant effect on the completeness of voluntary disclosure, while liquidity has a negative and insignificant effect on the completeness of voluntary disclosure. Simultaneous test results show that profitability, leverage and liquidity have a positive and significant effect on the completeness of voluntary disclosure.